Sub-Saharan Africa: Options for smallholder milk processing - O'Mahony, F.; Peters, Kurt J. (1987)
Describes some milk products that are suitable for manufacture at the smallholder level, the technologies required for small-scale manufacture of these products, and the product options available to smallholders.